2006
DOI: 10.1111/j.1747-0765.2006.00066.x
|View full text |Cite
|
Sign up to set email alerts
|

Extractability of major and trace elements from agricultural soils using chemical extraction methods: Application for phytoavailability assessment

Abstract: To assess soil-to-plant transfer of various elements more precisely, the concentrations of the elements extracted from soil samples using eight chemical solutions were compared with the results of a pot cultivation experiment of komatsuna (Brassica rapa L. var. perviridis) or buckwheat (Fagopyrum esculentum M.) using the soils. From agricultural fields in Aomori, Japan, 16 soil samples were collected. Elements in the samples were extracted using acids (CaCl 2 ) and pure water. The 28 elements in the extracted … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
25
0

Year Published

2007
2007
2021
2021

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 48 publications
(27 citation statements)
references
References 32 publications
2
25
0
Order By: Relevance
“…The labile fraction of a soil is generally considered to consist of the 'exchangeable' cations that are removable from soil components. On an operational point of view, this 'exchangeable fraction' corresponds to cations that are leached from solid soils with buffered solutions such as ammonium acetate, ammonium chloride or ammonium nitrate (Tessier et al, 1979;Stewart et al, 1998;Takeda et al, 2006Takeda et al, , 2008International Organization for Standardization 19730, 2008). This method extracts cations from pore waters and those bounded to exchange sites on minerals and organic matter.…”
Section: A C C E P T E D Accepted Manuscriptmentioning
confidence: 99%
See 2 more Smart Citations
“…The labile fraction of a soil is generally considered to consist of the 'exchangeable' cations that are removable from soil components. On an operational point of view, this 'exchangeable fraction' corresponds to cations that are leached from solid soils with buffered solutions such as ammonium acetate, ammonium chloride or ammonium nitrate (Tessier et al, 1979;Stewart et al, 1998;Takeda et al, 2006Takeda et al, , 2008International Organization for Standardization 19730, 2008). This method extracts cations from pore waters and those bounded to exchange sites on minerals and organic matter.…”
Section: A C C E P T E D Accepted Manuscriptmentioning
confidence: 99%
“…The Sr content of this fraction is clearly linked to the nature of the geological bedrock and to the pedogenic processes that combine mainly the primary minerals alteration and the availability of the organic matter, but it is also controlled by rainfall . Many consider the reservoir consisting of the exchangeable cations to be the major source of base cations for the uptake by the vegetation (Blum, 2000;Gastberger et al, 2000;Takeda et al, 2006;Durante et al, 2013;van der Heijden et al, 2013;Bedel et al, 2016).…”
Section: A C C E P T E D Accepted Manuscriptmentioning
confidence: 99%
See 1 more Smart Citation
“…Several studies have shown the suitability of weak neutral salt solutions as metal extractants in soils because they can be considered good models for simulating rainfall and flooding events. Although there is no established standard method for these types of studies, the use of a 0.01-mol L −1 calcium chloride solution is widely recommended for the leaching of heavy metals present in exchangeable fractions of soils (Houba et al 2000;Kabata-Pendias 2004;Pueyo et al 2004Pueyo et al , 2005Sahuquillo et al 2003;Takeda et al 2006). Similarly, phosphate or acetate solutions have been reported to be better extractants for estimating the bioavailable arsenic in contaminated soils (Anawar et al 2008;Antosiewicz et al 2008;Moreno-Jiménez et al 2010).…”
Section: Introductionmentioning
confidence: 96%
“…Ammonium acetate (NH 4 Ac) extraction has been used to examine the association of radiocesium with clay minerals (e.g., Tsumura et al 1984;Roig et al 1998;Takeda et al 2006). The percentage of 137 Cs in the NH 4 Ac-extractable fraction is shown in Table 3.1.…”
Section: Chemical Extractionmentioning
confidence: 99%